Pemanfaatan Aplikasi BlueSPP Pada Android Untuk Pengontrolan Lampu Berbasiskan Mikrokontroler Arduino - Heri Hardi (UIN Sunan Kalijaga Yogyakarta, 2023)
The lamp is a lighting tool that is very widely used in everyday life as a means of lighting. The lamp will work or can be used if the lamp is given a power source or voltage. In general, to turn on the lights, we still do it manually, namely pressing the switch as a current or voltage connector for the lamp. However, if done manually it can be an obstacle for those who are busy, so that turning on the lights in their room has difficulty or takes time. Based on the problems above, here the author will design a plate that can be used to make it easier to turn on or control the lights in a room or house. In this case, the author uses a BlueSPP application on the PlayStore using Android Bluetooth and the Arduino interface uses Bluetooth HC-05. This equipment has a working system that is easy for anyone to use, control will be carried out by sending messages from the BlueSPP application via Bluetooth between the Android smartphone and the Arduino microcontroller. When the user sends a message from the BlueSPP Application, the Bluetooth HC-05 will receive commands from the application and forward it to Arduino as a data processor for the message to be instructed to relay whether to turn it on or off. In testing this equipment can work with a maximum range of 15 meters without any obstacles and a maximum work of about 8 meters when there are obstacles.